2015
DOI: 10.1109/ted.2015.2388788
|View full text |Cite
|
Sign up to set email alerts
|

Refined Conformal Mapping Model for MOSFET Parasitic Capacitances Based on Elliptic Integrals

Abstract: In this paper, the main MOSFET parasitic capacitances of planar devices (i.e., bulk, Fully depleted silicon-on-insulator (FDSOI), and planar double gate) are computed using two successive conformal mapping transforms. First, the structure is mapped to the real axis of the complex plane, and then the second transform, deduced directly from the Schwarz-Christoffel theorem, reduces the capacitance to the trivial parallel electrodes case. This second step involves elliptic integrals, which provide a generic expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…The same approach could be applied to Single-Gate MOSFETs. The parasitic capacitances are evaluated with the conformal mapping model reported in [21].…”
Section: Impact Of Overshoot On Ro Delaymentioning
confidence: 99%
“…The same approach could be applied to Single-Gate MOSFETs. The parasitic capacitances are evaluated with the conformal mapping model reported in [21].…”
Section: Impact Of Overshoot On Ro Delaymentioning
confidence: 99%
“…In this work, an accurate analytical parasitic capacitance model is proposed using the conformal mapping as well as Schwarz Christoffel transform [21], [28], [29], [32]. The proposed model is then verified with the 3D TCAD simulation, and the effect of important device parameters on the parasitic capacitance is investigated as well.…”
Section: Introductionmentioning
confidence: 99%
“…Charge sheet position values are varied [15][16][17][18] to provide for better outcome. It has been found that an epitaxial [8] oxide layer of BaTiO 3 -SrTiO 3 [19] as gate stack is way better than the other two and provides high accuracy of results [20][21][22][23] despite the presence of trap Charges [24] along the charge sheet position. Also, Conformal Mapping [17,18] is used in which Schwarz-Christoffel Transformation [20,21] has been employed for conversion of function to imaginary plane.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that an epitaxial [8] oxide layer of BaTiO 3 -SrTiO 3 [19] as gate stack is way better than the other two and provides high accuracy of results [20][21][22][23] despite the presence of trap Charges [24] along the charge sheet position. Also, Conformal Mapping [17,18] is used in which Schwarz-Christoffel Transformation [20,21] has been employed for conversion of function to imaginary plane. These concepts are applied to solve for surface potential due to trap charges and their influence on the Barium Titanate, a very high-k dielectric material.…”
Section: Introductionmentioning
confidence: 99%